Density Functional Theory Study on the Effect of Isomorphic Substitution of FAU Molecular Sieve on N2 Adsorption Performance. (22nd October 2021) - Wang, Mengya; Cao, Rong; Xia, Jiezhen; Zhao, Luchao; Li, Yong; Ciren, Qimi; Zhao, Dongye; Wang, Shifeng; Du, Chun; Wu, Qi
Abstract : Low pressure and anoxia are the main characteristics of the environment in the Tibetan Plateau, which means people living there have a large demand for oxygen to reduce the symptoms of altitude sickness. Pressure swing adsorption (PSA) is a competitive oxygen production technology in plateau areas, which relies on the molecular sieves for the separation of N2 and O2 in industry and portable medical equipment. The adsorption characteristics of the Faujasite-type (FAU) molecular sieves, as one kind of the most widely used adsorbents for O2 production, depend on the properties, amount, and distribution of the skeleton cations and atoms. In this paper, we explore the isomorphic substitution effect on the adsorption properties of N2 in FAU molecular sieves using the computational approaches based on the density functional theory (DFT). The structural analysis and adsorption energy calculated for the Zn, Ca, and Ga substitutions at the Si/Al skeleton sites in the β -cage structure, the basic unit of FAU molecular sieves, prove that the isomorphic substitution effect can strengthen the adsorption of N2 . The Bader charge and density of states analysis validate the formation of electron-deficient holes near the Fermi level and hence strengthen the local polarity of the pore structure and enhance the adsorption of N2 molecules. The work about isomorphic substitution on the FAU molecular sieves might provide an insight into heteroatom isomorphic modification mechanisms and designing excellent air separation materials.